Tourism Impact on the Environment in Nusa Penida Tourism Area - SUDIPA, Nyoman; MAHENDRA, Made Sudiana; ADNYANA, Wayan Sandi; PUJAASTAWA, Ida Bagus (Journal of Environmental Management and Tourism, 2020)
The growth of tourism in Nusa Penida is causing pressure on the environment, where tourism is causing land use change. Tourism is also causing environmental impacts due to the inclusion of pollutant sources from activities in land and coastal areas which results in a decrease in the quality of ground water, well water, and sea water.The analysis of this study is the calculation of land acquisition in the Nusa Penida Tourism Area by using a google map that has been digitized and a map of the earth from quick bird satellite imagery. With the baseline map used in 2003 with a map of land use in 2019 with overlay techniques. To calculate the quality of ground water, well water, and sea water counted with and as a comparison material using a water quality test based on an analysis study of the Environmental Impact of the Nusa Penida Tourism Area Year 1998.Land use change in Nusa Penida from 2003 to 2019 reached 164.84 ha or the rate of land use change in Nusa Penida of 0.85%. The results of the quality tests for sea water, well water and spring water in 2019 were better than the results of sea water quality testing, ground water and well water in 1998.. Parameters that affect the index of sea water pollution, ground water and well water in Nusa Penida are the parameters turbidity, free ammonia (NH 3 -N) dissolved residue (TDS) and total coliform.